Abiotic surrogates for temperate rocky reef biodiversity: implications for marine protected areas. Issue 3 (30th September 2013) - Rees, Matthew J.; Jordan, Alan; Price, Owen F.; Coleman, Melinda A.; Davis, Andrew R.; Defeo, Omar
Abstract Aim To examine the potential of remotely sensed abiotic measures as surrogates for the abundance, diversity and community composition of temperate rocky reef fishes and sessile invertebrates. Location Batemans Marine Park, south‐eastern Australia. Methods We used high‐resolution bathymetric side‐scan sonar imagery to quantify abiotic measures of rocky reef habitat, within a marine protected area (MPA), and examine the relationship between abiotic measures and (1) sessile invertebrate abundance, (2) sessile invertebrate species richness, (3) total fish abundance, (4) fish species richness, and (5) Monacanthidae abundance using generalized additive mixed models (GAMMs). We chose GAMMs as the preferred statistical analysis to account for the spatial autocorrelation present in our data. Results We found a strong positive relationship between abiotic measures and sessile invertebrate abundance and diversity (r2 > 0.64). By far the most important predictor was vertical relief within a 75 m radii seascape surrounding the faunal survey. Overall, abiotic measures were poor predictors of total fish abundance (r2 = 0.175) and fish species richness (r2 = 0.276), with minimum adequate models producing low explanatory power. In contrast, Monacanthids exhibited a strong positive relationship with abiotic variables (r2 = 0.385), with increased abundance associated with greater depth and distance from soft sediment. Main conclusions Remotely sensed abiotic measures are important predictors in describing the spatial patterns of sessile invertebrate abundance and diversity and Monacanthid abundance. In contrast, abiotic variables were poor predictors of total fish abundance and diversity. Habitat could be a useful cost‐effective surrogate to determine areas of conservation value for certain temperate rocky reef assemblages. This information is valuable for future MPA development and design.